2015
DOI: 10.1590/0103-8478cr20131457
|View full text |Cite
|
Sign up to set email alerts
|

Aplicação em pré-colheita de cloreto de cálcio no controle do despencamento natural dos frutos de bananeira 'FHIA-18'

Abstract: RESUMO O objetivo deste trabalho foi avaliar o efeito da aplicação de CaCl 2 em pré-colheita, em diferentes doses e épocas no controle do despencamento natural de frutos da

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…The highest firmness observed in the second production cycle can be attributed to climatic conditions and fruit nutrient availability, which vary throughout the cycles. According to Pereira et al (2015), fruits with greater firmness are less susceptible to plummeting. Therefore, the increase in this variable is interesting, especially in relation to 'FHIA 18', which present problems with the natural fruits' detachment.…”
Section: Physicochemical Characterization From Ripe Fruits Of Bananamentioning
confidence: 99%
See 1 more Smart Citation
“…The highest firmness observed in the second production cycle can be attributed to climatic conditions and fruit nutrient availability, which vary throughout the cycles. According to Pereira et al (2015), fruits with greater firmness are less susceptible to plummeting. Therefore, the increase in this variable is interesting, especially in relation to 'FHIA 18', which present problems with the natural fruits' detachment.…”
Section: Physicochemical Characterization From Ripe Fruits Of Bananamentioning
confidence: 99%
“…is one of the most important fruit crops of the world. In Brazil, the fruit production is mainly concentrated in cultivars belonging to Prata and Cavendish groups, which have high productive potential, but are susceptible to fungal diseases that are major threats to crops (Pereira et al, 2015). Therefore, other banana genotypes have been recommended, such as the 'FHIA 18', a tetraploid hybrid (AAAB) developed from crosses between Prata Anã cultivar by the Honduran Foundation for Agricultural Research (FHIA).…”
Section: Introductionmentioning
confidence: 99%
“…Due to high perishability, particularly during ripening of fruits, changes in various biochemical components like carbohydrate composition, cell wall adhesion, formation of volatile compounds and chlorophyll degradation take place which ultimately lead to weakening of fingers and detachment from its stalk. Fiber content, structure of the cell wall and degradation of the macromolecular constituents of the cell wall are the factors that lead to rupture of pedicel (Pereira et al, 2015;Castricini et al, 2015) [13,3] . It was also observed that dropping may occur due to the faster degradation in amount of structural components of cell walls from parenchyma cells (Mbeguie et al, 2009) [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Physical, chemical and physicochemical transformations are the main causes of quality loss during storage. Thus, the storage carried out in a suitable way becomes of great value so that such transformations do not harm the commercialization, as well as the use of post-harvest technology that allows to preserve the quality of the fruits (PEREIRA et al, 2015).…”
Section: Introductionmentioning
confidence: 99%